Association between Socialization and the Use of Maternity Waiting Home in East Aceh, Indonesia - Dari, Atika Triwulan; Zulfendri, Zulfendri; Aulia, Destanul (Journal of Health Policy and Management, 2019)
Background: Maternity waiting homes are residential facilities where women who live remotely can wait before giving birth at a hospital or health center. The aim of implementing maternity waiting for home strategy is to reduce maternal and perinatal mortality by improving access to skilled birth attendance and emergency obstetric care, particularly for women in rural and remote areas. This study aimed to examine the association between socialization and the use of maternity waiting home in East Aceh.Subjects and Method: This was a cross-sectional study carried out at four community health centers (puskesmas), in East Aceh, Indonesia. A sample of 130 pregnant mothers was selected for this study by stratified random sampling. The dependent variable was the use of a maternity waiting home. The independent variable was socialization and family support. The data were collected by questionnaire and analyzed by multiple logistic regression.Results: Socialization was associated with increased use of maternal waiting home (OR= 14.17; p= 0.002), after controlling from the effect of family support.Conclusion: Socialization is associated with increased use of maternal waiting home, after controlling for the effect of family support.Keywords: maternity waiting home, socialization, family support.Correspondence: Atika Triwulan Dari. Masters Program in Public Health, Universitas Sumatera Utara, Jalan Universitas No. 21, Universitas Sumatera Utara, Medan 20155, North Sumatera, Indonesia. Email: atika.triwulandari@ymail.com.Journal of Health Policy and Management (2019), 4(2): 86-90https://doi.org/10.26911/thejhpm.2019.04.02.02